2011
DOI: 10.1029/2009rs004327
|View full text |Cite
|
Sign up to set email alerts
|

Case study of apparent longitudinal differences of spread F occurrence for two midlatitude stations

Abstract: [1] Spread F is a widely studied subject, and the occurrence of spread F is affected by many factors. One of these factors is acoustic gravity waves (AGWs) which are very important in seeding spread F. Since most of the AGWs in the ionosphere originate from the lower atmosphere, there should be some regional features of spread F due to the different meteorological or ground conditions immediately beneath the local ionosphere. In this paper, a data set with a time coverage of one solar cycle from two Chinese st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 43 publications
8
18
0
Order By: Relevance
“…The occurrence of nighttime midlatitude spread F has been well documented in the literature considering seasonal, solar and geomagnetic variability (Bowman, 1960, Singleton, 1968Rastogi, 1977;1990;Huang et al, 2011). In the present study, efforts have also been made to examine the monthly occurrence of different types of spread F. It can often be observed that in the nighttime midlatitude ionosphere, various mechanisms are considered as candidates to initiate instability conditions for the formation of irregularities at the bottom of F layer which develop into certain diffused irregularity traces termed as RSF.…”
Section: Monthly Variation Of Different Spread F Typesmentioning
confidence: 83%
See 2 more Smart Citations
“…The occurrence of nighttime midlatitude spread F has been well documented in the literature considering seasonal, solar and geomagnetic variability (Bowman, 1960, Singleton, 1968Rastogi, 1977;1990;Huang et al, 2011). In the present study, efforts have also been made to examine the monthly occurrence of different types of spread F. It can often be observed that in the nighttime midlatitude ionosphere, various mechanisms are considered as candidates to initiate instability conditions for the formation of irregularities at the bottom of F layer which develop into certain diffused irregularity traces termed as RSF.…”
Section: Monthly Variation Of Different Spread F Typesmentioning
confidence: 83%
“…It can be observed that during 21:15 to 21:30 UT, the nighttime F region plasma density distribution was affected by irregularity distributions, which reappeared during 22:30 to 22:45 UT and could be related to spread F development over the European longitudes. As 3rdAugust 2015 was a magnetically quiet day, the sudden plasma depletion observed may indicate the generation of local irregularities under the influence of gravity waves which may originate from the lower atmosphere and trigger the instability at the bottom of the F layer (Huang et al, 2011).The focus of the present paper is limited to three ionosonde stations of European longitude sector, namely, Nicosia, Athens and Pruhonice. The stations at Nicosia and Athens are situated at around 35°to 37°N latitude whereas Pruhonice is at higher latitude (∼50°N).…”
Section: Case Study Of 3rd August 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is exactly the same as shown here and in ref. [5] Further indication of the longitudinal difference between the two stations was shown in the spread-F occurrence [21]. With proper zonal wind information, it will be possible to explain the observed differences in electron density over the two stations in terms of magnetic declination and zonal winds.…”
Section: Longitudinal Variations For Other Sectorsmentioning
confidence: 96%
“…Hoang et al (2010) performed a comparative study of the ESF characteristics over two equatorial sites, Ho Chi Minh in Vietnam and São Luis in Brazil, showing that the spread-F occurrence is significantly less frequent at Ho Chi Minh than at São Luis throughout the year. Huang et al (2011) considered two Chinese stations, Changchun and Urumqi, at the same latitude and separate in longitude by 38 degrees, and they showed that the spread-F occurrence is always larger at Changchun than at Urumqi. This paper describes a comparative study of spread-F occurrence over five low-latitude sites ( Fig.…”
Section: Introductionmentioning
confidence: 99%